2016
DOI: 10.4103/2152-7806.191075
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the length of stay in patients with lumbar pedicle screw fixation

Abstract: Background:Current health care practices aim for cost reduction to achieve maximal benefit. Because of the increasing number of spinal fusions, this area has become a target for both hospitals and payment organizations. Length of stay (LOS) is one potentially modifiable variable to help reduce overall cost. Attempting to predict the LOS in spinal surgery based on patient factors has not revealed a set of variables that are consistently associated with increased stay.Methods:Medical records from all patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In one study, Wang et al reported the median LOHS was three days for both the IPD and tubular/percutaneous BPS fixation group, but four days in the open BPS fixation group [ 1 ]. El-Kadi et al reported patients who underwent UPS and/or BPS by one surgeon at one facility, had positive correlations with LOHS, indicating that those with higher age and BMI would be expected to have a longer length of stay [ 25 ]. Segura-Trepichio et al reported LOHS was significantly lower in the discectomy plus ISP when compared to the PLIF group with microdiscectomy, with an average LOHS of two days versus an average LOHS of five days(P < 0.01) [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…In one study, Wang et al reported the median LOHS was three days for both the IPD and tubular/percutaneous BPS fixation group, but four days in the open BPS fixation group [ 1 ]. El-Kadi et al reported patients who underwent UPS and/or BPS by one surgeon at one facility, had positive correlations with LOHS, indicating that those with higher age and BMI would be expected to have a longer length of stay [ 25 ]. Segura-Trepichio et al reported LOHS was significantly lower in the discectomy plus ISP when compared to the PLIF group with microdiscectomy, with an average LOHS of two days versus an average LOHS of five days(P < 0.01) [ 26 ].…”
Section: Reviewmentioning
confidence: 99%